EDJ 2021
DOI: 10.12944/edj.03.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implantitis Matter: Possibilities of Treatment but Without a Strong Predictability for Solution

Abstract: Dental implants are one of the revolutionary tools in the rehabilitation of patients' functions and esthetics, presenting high long-term success rates. In 2015, it was estimated about 3 million people in the US on having dental implants and it is increasing by 500,000 per year, solely in the US. Despite the high survival rate at 10 years (around 96%), 1 there is a risk for complications, such as peri-implantitis. 2 It is an inflammatory disease, commonly a plaque-associated condition, affecting directly the Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Even though the implant survival rate may have achieved more than 90% in the long-term [2,32,33], the presence of MBL may permit implant thread exposition, leading to an easy bacterial accumulation and consequent peri-implant diseases, with possible implant loss [8,34,35]. The objective of this systematic review was to answer a specific clinical question, comparing the results between EH and MT implants when assessed within the same study (reducing bias).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the implant survival rate may have achieved more than 90% in the long-term [2,32,33], the presence of MBL may permit implant thread exposition, leading to an easy bacterial accumulation and consequent peri-implant diseases, with possible implant loss [8,34,35]. The objective of this systematic review was to answer a specific clinical question, comparing the results between EH and MT implants when assessed within the same study (reducing bias).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the loss of supporting bone and soft tissue inflammation ( Berglundh et al, 2019 ), reaching a pocket depth (PD) of ≥ 6 mm, bleeding upon probing (BoP), or suppuration and radiographic bone loss (RBL) ≥ 3 mm ( Berglundh et al, 2018 ). Then, the main goal of peri -implantitis treatment is to eliminate inflammation, preserve the structure around the implant, and bring a healthy status to the tissues ( de Waal et al, 2013 , Fernandes, 2021b ). Moreover, some authors reported that PI is between 2.7% and 47.1%, and the success rate in high-risk groups (patients with a family or personal history of periodontitis and smokers) can be around 70% ( Zitzmann et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%